Effect of frequency in roller ski skating - Sandbakk, O.; Leirdal, S.; Ettema, G. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The effect of movement frequency has been extensively studied in endurance Sports like cycling. It is believed that frequency affects both efficiency and performance in endurance Sports. The purpose of the present study was to examine the effect of frequency on efficiency at different work rates and on performance using the G3 skating technique.